Dimorphisim In Nuclear Polyhedrosis Virus (Bmnpv) (Family: Baculoviridae) Causing ‘grasserie’ Disease In Silkworm (Bombyx Mori L.): Light And Electron Microscopy And Protein Profile (Applied Biological Research, 2012)
The present study was aimed to microscopically assess dimorphism in nuclear  polyhedrosis virus (BmNPV) responsible for ‘Grasserie’ disease in silkworm,  Bombyx mori L. Tissue sections of infected larvae integument were found  ruptured, had abundant lump cells and released milky fluid containing occluded bodies (OBs). Nuclei of columnar epithelial cells of integument were almost covered with BmNPV polyhedra. Scanning electron micrograph  (SEM) revealed full lesions in infected integuments with very fragile hypo dermis. Transmission electron micrograph (TEM) showed that infecteddifferent parts of peripheral membrane contain lipid globules started to  diffuse continuously to form a large structure to occupy maximum OBs.  In advanced stage of infection, two viral phenotypes were noticed. 1st form  occluded within polyhedra was responsible for primary infection in mid-gut  cells. The 2nd form ‘budded virus (BV)’ never became occluded and was  released into haemolymph and spread infection bycell to cell contact within  insect body. The fully transformed lipid globules discharged the 1st form  whereas BV was observed in integument, mid gut and Malpighian  tissues. Interestingly, the infected mid gut cells were dilated in presence of  OBs and gradually increased in number to form chain-like structure which  broke up no sooner the number of OBs reached highest carrying capacity,  releasing polyhedra in gut juice. Inner layer of infected Malpighian tissues  were loose and fragmented with OBs in between the striations of Malphigian  cells. BVs, the new finding from B. mori, are responsible for virulence of BmNPV in silkworm. 29 and 17 kDa proteins in multivoltine (Nistari) and  bivoltine (NB4D2), respectively, were absent in the haemolymph of BmNPV  infected counterpart. The total quantity of haemolymph protein was more in  multivoltine samples than in bivoltine samples.
Keywords: Bombyx mori; budded virus; Grasserie; polyhedra; occluded bodies; innate immune system